A new method for isomorphism identification in topological graphs using incident matrices - Yang, Fei; Deng, Zongquan; Tao, Jianguo; Li, Lifang (Mechanism and machine theory, 2012)
A new method using incident matrices to identify the isomorphism of topological graphs is proposed in this paper. The technique of acquiring the necessary condition for identifying the isomorphism is developed by comparing the calculation of incident matrices. Furthermore, it can be automatically executed by programs. With the help of the results from the necessary condition, the technique to find the correspondence of different vertices is presented, and the sufficiency for the isomorphism identification is obtained. Three examples are presented to demonstrate the validity and reliability of this method. ► We developed a new method to detect the isomorphism with structural synthesis. ► Using incident matrices, the necessary condition was obtained. ► On the basis of the necessary condition, the sufficiency was achieved. ► Detail operations to get the sufficient and necessary conditions were given. ► The new method can find the sufficiency quickly, it is effective and reliable.